2018
DOI: 10.1002/jcph.1089
|View full text |Cite
|
Sign up to set email alerts
|

Multistep Unified Models Using Prior Knowledge for the Prediction of Drug Clearance in Neonates and Infants

Abstract: Allometric approaches are widely used for interspecies scaling for the prediction of pharmacokinetic (PK) parameters during drug development. The concept of allometry can also be extended to predict PK parameters from adults to children. Three methods for extrapolating pediatric clearance were developed and evaluated using the clearance values of 4 drugs. The first method was established using a simple allometric (SA) model with estimated coefficient and exponent based on data ranging from children older than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…We noted a relatively less precise prediction of clearance in children ≤2 years of age vs older children (>2 years of age). This is not surprising since previously published allometric, mechanistic, and PBPK models also demonstrated similar observations 16,30–33 . For example, a comparison between PBPK and allometric scaling (using an age‐dependent exponent) showed that both models provided a similar magnitude of precision for clearance prediction in children ≤2 years of age, which was slightly lower than the older children 16 .…”
Section: Discussionsupporting
confidence: 61%
“…We noted a relatively less precise prediction of clearance in children ≤2 years of age vs older children (>2 years of age). This is not surprising since previously published allometric, mechanistic, and PBPK models also demonstrated similar observations 16,30–33 . For example, a comparison between PBPK and allometric scaling (using an age‐dependent exponent) showed that both models provided a similar magnitude of precision for clearance prediction in children ≤2 years of age, which was slightly lower than the older children 16 .…”
Section: Discussionsupporting
confidence: 61%
“…Such preliminary data combined with further clinical validation could provide information on clinical drug medication in neonates. 47,48…”
Section: Discussionmentioning
confidence: 99%
“…To calculate the optimal doses, we used the range of 0.3–0.6 μg/L as the PK target for efficacious and safe analgesia [21], while higher levels have been described for anaesthetic effects in the literature [26]. Currently, the usual induction and maintenance doses of sufentanil are 0.25–2.0 and 0.5–1.5 μg/kg/h, respectively [11, 27-29]. Our results indicate that the respective doses of 2.13 μg/kg and 0.29 μg/kg/h could be used.…”
Section: Discussionmentioning
confidence: 99%